The Effect of Capital Structure (DER And DAR) On ROA Of Industrial Goods Sub-Sector Companies Listed on The Indonesia Stock Exchange - Eva Sriwiyanti; Wico J Tarigan; Diana L Hutagalung (Program Studi Akuntansi Universitas Simalungun, 2026)
This study is motivated by the importance of capital structure management in improving corporate profitability, particularly in the industrial goods subsector, which requires substantial funding. The study aims to analyze the effect of Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) on Return on Assets (ROA). A quantitative approach with an associative design was employed, using purposive sampling to select 12 companies with 60 observations during the 2020–2024 period. Secondary data were obtained from annual financial statements and analyzed using multiple linear regression, supported by classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results show that partially, DER and DAR do not significantly affect ROA, while simultaneously they have a significant effect. The Adjusted R Square value of 0.163 indicates limited explanatory power. Additionally, DER and DAR exhibit a negative relationship with ROA, implying that increased leverage does not necessarily enhance profitability